Visually navigated, ultrasound-guided, freehand percutaneous calyceal puncture – preclinical evaluation of a novel device to simplify a complex surgical task - Wakileh, Gamal Anton; Hohmann, Manuel; Rassweiler-Seyfried, Marie Claire; Klein, Jan Thorsten (Ultrasound International Open, 2024)
Purpose Freehand sonographic percutaneous puncture techniques for the renal calyceal system are on the rise. Much time and practice are required to master this technique. Navigation-supported puncture aids could help make percutaneous access easier and faster. The aim of this study was to determine whether navigated puncture is feasible, and whether it is easier and faster compared to the conventional sonographic procedure.Materials & Methods We performed prospective free-hand percutaneous puncture on a porcine kidney model embedded in gelatin using the Xperius ultrasound system in combination with needle tracking with a Stimuplex Onvision hollow needle, compared to the conventional freehand ultrasound puncture technique. Punctures were performed by 25 participants using the ultrasound machine with or without needle tracking mode.Results Compared to the conventional approach, the navigated approach reduced the number of puncture procedures by 0.2 attempts(8%) in the experienced group. The time to calyx access was reduced by 15 seconds (26%). In the novice group, navigated puncture required 1.2 fewer attempts (36%) and the time to access was 70 seconds faster (61%). Conclusion Puncture using the novel device is feasible. The number of punctures and the time needed for successful access of the calyceal system was reduced by use of navigation in both groups, although the trend was significant only in the novice group. Navigation using needle tracking seems to help beginners perform sonographic percutaneous puncture at a level similar to experienced users. For a more precise analysis and validation, further studies are needed.
Keywords: navigation; percutaneous kidney puncture; kidney stone surgery; renal access; PCNL